Oil Absorption Analysis of Vegetable Oil onto Kapok Fiber Using pH and Temperature - Sukor, Afiz; Arni Syafiqah; Rosniza Hussin (Journal of Advanced Mechanical Engineering Applications, 2025)
Oil spills pose serious environmental and economic threats, driving the search for sustainable sorbent materials. This study examines the effect of pH and temperature on the oil absorption performance of treated kapok fiber, a natural and hydrophobic material with a hollow tubular structure. Kapok fibers were treated and tested under varying pH (3, 7, and 11) and temperature (40 °C and 70 °C) conditions using coconut and canola oils. Characterization through SEM, FTIR, and contact angle analysis revealed that alkaline treatment effectively removed surface waxes, improving oil affinity while maintaining structural integrity. The highest oil uptake occurred under alkaline conditions (pH 11) and elevated temperature, indicating enhanced sorption efficiency. These results demonstrate the potential of chemically treated kapok fiber as an eco-friendly sorbent for oil spill remediation applications.